Population Periodicals. A Directory of Serial Population Publications in the ESCAP Region. Asian Population Studies Series No. 17 - United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand).; United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This publication has been prepared for government personnel, research workers, librarians/documentalists, teachers, and students. Contained within the directory are materials published in the Economic and Social Commission for Asia and the Pacific (ESCAP) region on population-related topics. The publication is arranged in four sections. The user's guide contains 21 keys, explaining the organization of the directory. A country index and subject index are included as a cross reference to the alphabetical title listing. The former is arranged alphabetically by country, with percentage, type of available population materials, and periodical entry numbers. Topics within the subject index are population projections, ecology, family planning, labor force, migration, mortality, population problems in legislation, rural population, urbanization, and vital statistics. Countries and accompanying entry numbers are found under each heading. The main section of the directory is the alphabetical title listing. Data elements for each title include the type, form, city, year, and language of publication, International Standard Serial Number (ISSN), periodicity, subscription address, pages, circulation, price, distribution, and microfilm availability. This directory serves as a resource in searching for literature, and establishing a program for systematic acquisition of materials. (BP)
Availability: Clearinghouse and Information Section, Population Division, ESCAP, Sala Santitham, Bangkok 2, Thailand/Sales Section, United Nations, New York, N.Y. 10017 (IX ISSN 0066-8451).
ERIC Note: The Country Index and Subject Index were printed on colored paper and may reproduce marginally.
Microfiche.
Keywords: Bibliographies; Demography; Directories; Environmental Education; Foreign Countries; Indexes; Information Retrieval; Periodicals; Population Education; Resource Materials; Asia -- Far East; Reference Materials, Directories/Catalogs.